Gastrointestinal symptoms and the severity of COVID‐19: Disorders of gut–brain interaction are an outcome. Issue 9 (5th April 2022) - Ebrahim Nakhli, Ramin; Shanker, Aaron; Sarosiek, Irene; Boschman, Jeffrey; Espino, Karina; Sigaroodi, Solmaz; Al Bayati, Ihsan; Elhanafi, Sherif; Sadeghi, Amin; Sarosiek, Jerzy; Zuckerman, Marc J.; Rezaie, Ali; et al.
Abstract: Background: Many of the studies on COVID‐19 severity and its associated symptoms focus on hospitalized patients. The aim of this study was to investigate the relationship between acute GI symptoms and COVID‐19 severity in a clustering‐based approach and to determine the risks and epidemiological features of post‐COVID‐19 Disorders of Gut–Brain Interaction (DGBI) by including both hospitalized and ambulatory patients. Methods: The study utilized a two‐phase Internet‐based survey on: (1) COVID‐19 patients' demographics, comorbidities, symptoms, complications, and hospitalizations and (2) post‐COVID‐19 DGBI diagnosed according to Rome IV criteria in association with anxiety (GAD‐7) and depression (PHQ‐9). Statistical analyses included univariate and multivariate tests. Results: Five distinct clusters of symptomatic subjects were identified based on the presence of GI symptoms, loss of smell, and chest pain, among 1114 participants who tested positive for SARS‐CoV‐2. GI symptoms were found to be independent risk factors for severe COVID‐19; however, they did not always coincide with other severity‐related factors such as age >65 years, diabetes mellitus, and Vitamin D deficiency. Of the 164 subjects with a positive test who participated in Phase‐2, 108 (66%) fulfilled the criteria for at least one DGBI. The majority ( n = 81; 75%) were new‐onset DGBI post‐COVID‐19. Overall, 86% of subjects with one or more post‐COVID‐19 DGBI had at least one GI symptom during the acute phase of COVID‐19, while 14% did not. Depression (65%), but not anxiety (48%), was significantly more common in those with post‐COVID‐19 DGBI. Conclusion: GI symptoms are associated with a severe COVID‐19 among survivors. Long‐haulers may develop post‐COVID‐19 DGBI. Psychiatric disorders are common in post‐COVID‐19 DGBI. Abstract : During the acute disease, symptomatic patients with positive COVID‐19 test results fell into one of five distinct clusters based on the appearance of GI symptoms, loss of smell, and chest pain. The presence of GI symptoms was associated with severe COVID‐19. Moreover, COVID‐19 with or without GI symptoms in the acute phase may lead to Disorders of Gut‐Brain Interaction (DGBI). Depression and anxiety are common in post‐COVID‐19 DGBI. .